FAKTOR-FAKTOR YANG MEMPENGARUHI STRUKTUR MODAL PADA PERUSAHAAN PUBLIK SEKTOR MANUFAKTUR - SEFTIANNE SEFTIANNE; RATIH HANDAYANI (Jurnal Bisnis dan Akuntansi, 2011)
Capital structure is the proportion between uses debt or equity. In specifying optimal, we must consider many things influencing it. The research was to analyzed the factors that influence to the capital structure companies joining the Jakarta Stock Exchange. The sample of this research consisting of 92 data that has been listing in Indonesian Stock Exchange for the period 2007 until 2009 that has been selected by purpose sampling method. This study uses multiple regression method to see the contribution of each variable in influence capital structure. The empirical result indicates that size and growth opportunity have influence to capital structure. Other independent variables (managerial ownership, business risk, profitability, liquidity and asset structure) do not have influence toward capital structure.